PENGARUH MODEL PEMBELAJARAN REACT TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS IX SMPN 7 PADANG - Iman, Yuna Dilil (Departemen Matematika, 2024)
Especially for students, communication skills are one of the most important aspects of the 21st century. Developing mathematical communication skills is an important part of learning mathematics. This skill is the focus of the study. Based on the results of the first test of mathematical communication skills and the results of the interviews conducted in Class IX SMPN 7 Padang, these students’ skills still need improvement. For this reason, the REACT model was used to compare the mathematical communication skills of students who implemented REACT learning with those who implemented conventional learning in Class IX SMPN 7 Padang. The research uses the type of research quasi experimental design with the research design is static group design. The population in this study was all the students in Class IX SMPN 7 Padang, and the sampling was done using simple random sample. The final essay test was given to both sample classes in order to compare the students’ ability levels. for data analysis using t-test. Therefore H0 is rejected. Students taught using REACT have better mathematical commmunication skills than students taught conventionally.Keywords– Mathematical Communication Ability, REACT Learning Model, Conventional Learning Model